Magnetic Resonance Parkinsonism Index for evaluating disease progression rate in progressive supranuclear palsy: A longitudinal 2-year study. (March 2020) - Quattrone, Aldo; Morelli, Maurizio; Quattrone, Andrea; Vescio, Basilio; Nigro, Salvatore; Arabia, Gennarina; Nisticò, Rita; Novellino, Fabiana; Salsone, Maria; Arcuri, Pierpaolo; Luca, Angelina; Mazzuca, Alessandro; et al.
Abstract: Introduction: We investigated the disease progression rate in patients with progressive supranuclear palsy-Richardson syndrome (PSP-RS) and PSP-parkinsonism (PSP-P) in comparison with Parkinson disease (PD) patients, using MRPI (Magnetic Resonance Parkinsonism Index), and MRPI 2.0. Methods: Fifteen PSP-RS patients (disease duration, y, mean ± SD: 2.5 ± 1.1), 16 PSP-P patients (disease duration, y, mean ± SD: 6.5 ± 3.2) and 19 PD patients (disease duration, y, mean ± SD: 3.2 ± 2.3) were enrolled. All patients underwent clinical assessment and MRI at baseline, 1-year, and 2-year follow-up. MRPI, MRPI 2.0 and clinical scores over 1 and 2-years were used to evaluate disease progression rate, and to calculate sample sizes required to power placebo-controlled trials. Results: All groups showed increased clinical motor scores over time whereas only PSP groups had increased MRPI and MRPI 2.0 values over T1 and T2 intervals. The percentage increase over 1 and 2-years of MRPI and MRPI 2.0 values was significantly higher in PSP groups than in PD group, and in PSP-RS than in PSP-P patients while no difference between patient groups was observed when clinical motor scores were considered. Sample size estimates showed that MRPI 2.0 performed better than MRPI and clinical scales. Treatment trials with MRPI 2.0 could be performed over 2-years both in PSP-RS and PSP-P with a sample size per treatment arm of 89 and 170 patients, respectively. Conclusions: Our results demonstrate that MRPI 2.0 was more powerful than MRPI and clinical motor scales in evaluating PSP progression, and in providing the best sample size estimates for clinical trials. Highlights: MRPI and MRPI 2.0 detected disease progression in PSP patients. MRPI 2.0 was more powerful than MRPI and motor scales in detecting PSP progression. MRPI 2.0 was the best measure for assessing sample size for clinical trials.